The Influence Of Leadership Style And Role Conflict On The Work Environment With Communication As An Intervening Variable In Bank Indonesia Representative Offices North Sumatra Province - Andy Saddam Ikhsan; Mesra B (Yayasan Multidimensi Kreatif, 2024)
Human resources (HR) is one part of organizational management that focuses on human resources. The task of human resource management is to manage the human element well in order to obtain a workforce that is satisfied with its work. In an organization, human beings are one of the most important elements in an organization. This study aims to see the Influence of Leadership Style and Role Conflict on the Work Environment with Communication as an Intervening Variable in the Bank Indonesia Representative Office in North Sumatra Province. The results of this study are as follows: Leadership Style has a positive and significant effect on Communication with the original sample value of 0.219 and p values of 0.017. Leadership Style had a positive and significant effect on the Work Environment with an original sample value of 0.362 and p values of 0.008. Communication had a positive and insignificant effect on the Work Environment with the original sample value of 0.224 and p values of 0.065,. Role Conflict had a positive and significant effect on the Work Environment with the original sample value of 0.680 and p values of 0.000. Role Conflict had a positive and insignificant effect on the Work Environment with the original sample value of 0.273 and p values of 0.053. Leadership Style had a positive and insignificant effect on the Work Environment through Communication with an original sample value of 0.049 and p values of 0.124. Leadership Role Conflict had a positive and insignificant effect on the Work Environment through Communication with an original sample value of 0.049 and p values of 0.124.